Digital Preservation of Rhodope Dialects Through Intelligent Language Technologies - Lazarova, Radomira; Tabakova-Komsalova, Veneta; Kanevska-Nikolova, Elena; Stoyanov, Stanimir (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The article presents a prototype intelligent language modelling system to preserve Rhodope dialects. Implemented in Prolog, it converts dialectal into standard Bulgarian lexical units and vice versa, generating the corresponding grammatical form. It includes a module for phonetic features and demonstrates the application of symbolic AI in digital cultural heritage.
Keywords: Rhodope Dialects; Digitalization; Prolog Logic Programming; Cultural Heritage